CHANGE OF INDICATORS CYTOKINE PROFILE IN ADOLESCENTS DEPENDING ON THE CHARACTERISTICS OF FOOD - E. D. Tselykh (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The analysis of cytokine status indicators in adolescents indigenous and migrant populations Khabarovsk Territory has revealed differences in their content depending on the power of quantitative and qualitative composition of the daily diet. Established ethnic characteristics cytokine profile associated primarily with the content of interferon's. Significantly higher concentration of cytokines IL-1β, IL-2, IL-4 and TNF-α and IFN-α was detected in peripheral blood serum of adolescents who are inmates of the orphanage in both ethnic groups, compared with adolescents living in a family environment. Correlations were defined between the content of proteins, fats, carbohydrates, vitamin C in diet and indicators of cytokines.